Product Market Competition and the Minimum Wage - Ronald Bachmann; Thomas K. Bauer; Hanna Kroeger (Verein für Socialpolitik, 2010)
This study analyzes employers' support for the introduction of minimum wages in order to improve their competitive position. Using a unique data set consisting of 800 firms in eight industries in the German service sector, we find some evidence that high-productivity employers support minimum wages to drive low-productivity firms out of the market. Furthermore, firms in highly competitive industries tend to support a minimum wage to prevent low-wage competition from other EU member states. In addition, there is strong evidence that members of employer associations are more likely to support a minimum wage when trade unions are weak.
Keywords: J38; J50; L41; 330; Minimum wage; product market competition; service sector